Spatio-Temporal Evolution of Sporulation in Bacillus thuringiensis Biofilm - El-Khoury, Nay; Majed, Racha; Perchat, Stéphane; Kallassy, Mireille; Lereclus, Didier; Gohar, Michel (Frontiers in Microbiology, 2016)
B. thuringiensis can produce a floating biofilm which includes two parts: a ring and a pellicle. The ring is a thick structure which sticks to the culture container, while the pellicle extends over the whole liquid surface and joins the ring. We have followed over time, from 16 h to 96 h, sporulation in the two biofilm parts. Sporulation was followed in situ in 48-wells polystyrene microtiterplates with a fluorescence binocular stereomicroscope and a spoIID-yfp transcriptional fusion. Sporulation took place much earlier in the ring than in the pellicle. In 20 h-aged biofilms, spoIID was expressed only in the ring, which could be seen as a green fluorescent circle surrounding the non-fluorescent pellicle. However, after 48 h of culture, the pellicle started to express spoIID in specific area corresponding to protrusions, and after 96 h both the ring and the whole pellicle expressed spoIID. Spore counts and microscopy observations of the ring and the pellicle harvested separately confirmed these results and revealed that sporulation occured 24 h-later in the pellicle comparatively to the ring, although both structures contained nearly 100% spores after 96 h of culture. We hypothesize that two mechanisms, due to microenvironments in the biofilm, can explain this difference. First, the ring experiences a decreased concentration of nutrients earlier than the pellicle, because of a lower exchange area with the culture medium. An second, the ring is exposed to partial dryness. Both reasons could speed up sporulation in this biofilm structure. Our results also suggest that spores in the biofilm display a phenotypic heterogeneity. These observations might be of particular significance for the food industry, since the biofilm part sticking to container walls - the ring - is likely to contain spores and will therefore resist both to washing and to cleaning procedures, and will be able to restart a new biofilm when food production has resumed.